1996
DOI: 10.1097/00006123-199605000-00004
|View full text |Cite
|
Sign up to set email alerts
|

The Neuroimaging and Clinical Spectrum of Neurofibromatosis 2

Abstract: Neurofibromatosis 2 (NF2) is an autosomal dominant disease predisposing to multiple tumors of the central and peripheral nervous system. Bilateral vestibular schwannomas are the hallmark of the disease. To define the clinical spectrum of the disease, we performed gadolinium-enhanced magnetic resonance imaging of the brain and spine as well as neurological, dermatological, and ocular examinations in 48 patients with NF2 diagnosed with the National Institutes of Health diagnostic criteria. Patients were ascertai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
144
1
5

Year Published

1997
1997
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 271 publications
(154 citation statements)
references
References 25 publications
0
144
1
5
Order By: Relevance
“…24 The tumor is more prevalent in the elderly population, with a peak incidence between the 6th and 8th decades.…”
Section: Discussion Demographic Featuresmentioning
confidence: 99%
“…24 The tumor is more prevalent in the elderly population, with a peak incidence between the 6th and 8th decades.…”
Section: Discussion Demographic Featuresmentioning
confidence: 99%
“…Its prevalence is estimated approximately at 1:60,000 [13] or less (1:87,410) [14]. The gold standard for diagnosis is the development of bilateral or unilateral vestibular schwannomas accompanied by hearing loss, tinnitus, and/or imbalance.…”
Section: Discussionmentioning
confidence: 99%
“…These include radiating pain accompanied by paresthesia, muscle weakness, atrophy, gait unsteadiness, and inturning of the foot. According to the report by Evans et al, [4] spinal tumors were discovered based on a clinical symptom (paresthesia) in only 1 (3.3%) of 30 children with NF2 aged < 10 years and Mautner et al [8] reported that spinal neurological symptoms were recognized only in 2 (4%) of 48 patients while spinal tumors were found in 43 (90%) among them. Thus, it is usually difficult to discover spinal tumors based on clinical manifestations and spinal tumors were discovered by screening MRI in most patients with NF2.…”
Section: Discussionmentioning
confidence: 99%